MULTISPIRAL COMPUTER TOMOGRAPHY IN DIAGNOSIS OF THE CONGENITAL DISEASE OF THE AORTA AND BRACHIOCEPHALIC ARTERIES IN CHILDREN FIRST YEAR OF LIFE - O. V. Valik; A. S. Ilin; D. B. Drobot; P. V. Teplov; N. I. Petrovskaya; A. V. Tokarev; K. A. Ilinykh (Креативная хирургия и онкология)
Aortic malformations often cause critical states in the neonatal period. MSCT method allows you to get a detailed understanding of the anatomy of vice and identify concomitant bronchopulmonary disease. This paper presents a comparative analysis of 27 patients of the first year of life with the pathology of the aortic arch, which were performed echocardiography and MSCT. After analysis of both research methods in 4 patients revealed a discrepancy echocardiography and MSCT data which led to a change in surgical approach. Just according to SITC 2 patients revealed tracheal stenosis, in one case, isolated, in another due to compression of the vascular ring. MSCT is a highly informative method for diagnosing pathology of the aortic arch and associated bronchopulmonary disease in children in the first year of life.